Effect of heat treatment on microstructures and mechanical properties of Al/Fe bimetal. Issue 12 (13th August 2018) - Jiang, Wenming; Li, Guangyu; Jiang, Zailiang; Wu, Yao; Fan, Zitian
ABSTRACT: The Al/Fe bimetallic castings were prepared by the compound casting combined with hot-dip galvanising and aluminising, and the effect of the heat treatment on microstructures and mechanical properties of the Al/Fe bimetallic castings was systematically studied in the present work. The thickness of the reaction layer of the Al/Fe bimetallic castings continuously increased with increasing solution temperature or prolonging solution time. However, the excessive solution temperature and solution time promoted cracks of the reaction layer. Regardless of as-cast or heat treatment, there were respectively the Fe2 Al5, Al9 Fe4 Si3, FeAl3, Al8 Fe2 Si and Al4.5 FeSi phases in the reaction layers. The nano-hardnesses of the reaction layer after heat treatment exhibited an increase compared to that of the as-cast condition.